ANALISIS KADAR TEMBAGA (Cu) DAN SENG (Zn) DALAM AIR MINUM ISI ULANG KEMASAN GALON DI KECAMATAN LIMA KAUM KABUPATEN TANAH DATAR - KHAIRA, KUNTUM (IAIN Batusangkar, 2014)
This research investigated the quantity of copper (Cu) and Zinc (Zn) in five mini- factories for processing water at Lima Kaum District, Tanah Datar Regency. The method used was atomic absorption spectrophotometry (AAS). The research findings revealed that the quantity of copper (Cu) fulfilled the criteria regulated by the Regulation of Ministry of Health Affairs No. 492/MENKES/PER/IV/2010. It is not exceed 2 mg/L. Meanwhile, the quantity of Zinc (Zn) did not fulfill, except one, the Regulation of Ministry of Health Affairs No. 492/MENKES/PER/IV/2010. It is because not exceed than 3 mg/L. Key words : secondry water, copper (Cu) and Zinc (Zn) atomic absorption spectrophotometry